Preliminary Evidence for Training-Induced Changes of Morphology and Phantom Limb Pain - Preißler, Sandra; Thielemann, Désirée; Dietrich, Caroline; Hofmann, Gunther O.; Miltner, Wolfgang H. R.; Weiss, Thomas (Frontiers in Human Neuroscience, 2017)
Abstract The aim of this study was to investigate whether a special prosthetic training in phantom limb pain patients aimed at increasing the functional use of the prosthesis leads to neural morphological plasticity of brain structures and a reduction in phantom limb pain. For chronic pain disorders, it was shown that morphological alterations due to pain might become at least partially reversed by pain therapies. Phantom limb pain is a chronic pain disorder that is frequently followed by neural plasticity of anatomical brain structures. In our study 10 patients with amputation of the upper limb participated in a two-weeks training with a myoelectric prosthesis with somatosensory feedback. Grip strength was fed back with electrocutaneous stimulus patterns applied to the stump. Phantom limb pain was assessed before and after the two weeks of training. Similarly, two T1 weighted MRI scans were conducted for longitudinal thickness analyses of cortical brain structures. As result of this treatment, patients experienced a reduction in phantom limb pain and a gain in prosthesis functionality. Furthermore, we found a change of cortical thickness in small brain areas in the visual stream and the postcentral gyrus ipsilateral to the amputation indicating morphological alterations in brain areas involved in vision and pain processing.